Proteomic analysis of posterior capsular plaques in congenital unilateral cataract. Issue 8 (3rd October 2018) - Van Looveren, Jan; Van Gerwen, Veerle; Schildermans, Karin; Laukens, Kris; Baggerman, Geert; Tassignon, Marie‐José
Abstract: Purpose: To obtain insights on the protein composition of posterior capsular plaques (PCP) in congenital unilateral cataract with anterior vitreolenticular interface dysgenesis (AVLID). Methods: Posterior capsular plaque's were collected during surgery in children presenting with congenital unilateral cataract. Surgeries were analysed focusing on the type of cataract, the integrity of the posterior capsule after peeling the PCP and the presence of vitreolenticular adherences when performing primary posterior capsulorhexis. Proteome analysis was performed on the collected PCPs. Results: Posterior capsular plaques collection and proteome analysis were feasible from four children presenting with unilateral idiopathic congenital cataract and AVLID. A large portion of the proteins found in the PCPs was similar to the proteins known to be present in lens epithelial cells and fibres. Proteins like vimentin, fibronectin, collagen type I, collagen type VI and lumican were also found, which typically are present in mesenchymal tissue but not in lens tissue or capsule. Conclusion: Posterior capsular plaques in cases of unilateral idiopathic congenital cataract of the AVLID type present a protein composition of mainly proteins found in lens epithelial cells and fibres. Some proteins however are a specific for lens tissue and are typically seen in mesenchymal tissue.